2020
DOI: 10.1155/2020/9593516
|View full text |Cite
|
Sign up to set email alerts
|

Saponin Facilitates Anti-Robo1 Immunotoxin Cytotoxic Effects on Maxillary Sinus Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers worldwide. The standard treatment of surgery, chemotherapy, and radiotherapy can result in long-term complications which lower the patient’s quality of life, such as eating disorders, speech problems, and disfiguring or otherwise untoward cosmetic issues. Antibody therapy against cancer-specific antigens is advantageous in terms of its lesser side effects achieved by its greater specificity, though the antitumor activity is still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…One explanation for this result is that the fish culture cell lines used in our study may be more sensitive to the action of saponins, an issue to look into in future in vitro studies using fish cells lines. The toxicity in the fish cell line used here was very similar to those observed in vitro, conducted using quillaja saponin extracts on human gastric cancer cells lines SNU1 and KATO III [70], and human maxillary sinus squamous cancer cell lines HNSCC [71] showed similar toxicity results (13 to 67 µg/mL). These results suggest that cancer cell lines may have changed the structure of the cell membrane, as supported by previous studies [72].…”
Section: Discussionsupporting
confidence: 78%
“…One explanation for this result is that the fish culture cell lines used in our study may be more sensitive to the action of saponins, an issue to look into in future in vitro studies using fish cells lines. The toxicity in the fish cell line used here was very similar to those observed in vitro, conducted using quillaja saponin extracts on human gastric cancer cells lines SNU1 and KATO III [70], and human maxillary sinus squamous cancer cell lines HNSCC [71] showed similar toxicity results (13 to 67 µg/mL). These results suggest that cancer cell lines may have changed the structure of the cell membrane, as supported by previous studies [72].…”
Section: Discussionsupporting
confidence: 78%
“…Since photosensitizer administration and light exposure enhanced the cytotoxic effect of IT-ROBO1 enormously, we concluded that the cytotoxicity results from the problem of endosomal escape (10,11,18). This was also supported by our observation that treatment with saponin, which facilitates the internalization of IT, and the endosomal release of saporin, augmented cytotoxicity and enhanced the tumor-reducing effect both in vitro and in vivo (24).…”
Section: Discussionsupporting
confidence: 64%
“…It was subsequently reported that ROBO1 is specifically expressed in a wide range of malignant cells or neoangiogenic endothelial cells (21,22). Thus, ROBO1 has been widely studied as a good molecular target for cancer therapy (7,8,14,16,18,(21)(22)(23)(24). Maiti et al reported the expression of ROBO1 in HNSCC (23).…”
Section: Discussionmentioning
confidence: 99%
“…This molecule does not have a natural cell‐binding domain and is active only when transferred to the cytosol after endocytosis. 18 , 19 The antitumor principle of the iTAP method involves a high concentration of saporin delivered to cancer cells, specifically by cetuximab, which accumulates in endosomes. Subsequently, on laser irradiation of NPe6, the photodynamic effect causes saporin to translocate from the endosome to the cytosol, leading to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Saporin is a toxic protein with a molecular weight of ~30 kDa and is classified as a type 1 ribosome‐inactivating protein (RIP) isolated from the plant Saponaria officinalis . This molecule does not have a natural cell‐binding domain and is active only when transferred to the cytosol after endocytosis 18,19 . The antitumor principle of the iTAP method involves a high concentration of saporin delivered to cancer cells, specifically by cetuximab, which accumulates in endosomes.…”
Section: Introductionmentioning
confidence: 99%